Desain dan Analisis Sistem Akses Terkendali ke Aplikasi LIMS ISO 17025:2017 Menggunakan Firewall dan VPN di Laboratorium Kalibrasi PT SPIN - Kurniawan Hidayat; Ari Purno Wahyu Wibowo (Yayasan Literasi Sains Indonesia, 2026)
Data security and traceability are crucial aspects for calibration laboratories to meet the ISO/IEC 17025:2017 standard. LPT SPIN already uses a Laboratory Information Management System (LIMS) for data management, but the system is still limited to a local network and does not yet have secure remote access facilities. This condition poses operational obstacles as well as information security risks that can impact the fulfillment of accreditation requirements. This study aims to design and analyze a controlled access system to the LIMS application using a firewall and Virtual Private Network (VPN) to improve security and access flexibility in accordance with ISO/IEC 17025:2017. The research methods used are a descriptive approach to analyze the existing system and an experimental approach to design, implement, and test the proposed system. The implementation was carried out by applying a firewall as a network traffic controller and a VPN as an encrypted remote access medium. The results showed that the designed system was able to improve network security, restrict access to authorized users only, and enable remote access to the LIMS application without significantly compromising system performance. In addition, the proposed system design was considered to have met the information security and access control principles required in ISO/IEC 17025:2017.